2001
DOI: 10.1152/ajpgi.2001.281.1.g191
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor inhibits glycylsarcosine transport and hPepT1 expression in a human intestinal cell line

Abstract: The human intestinal cell line Caco-2 was used as a model system to study the effects of epidermal growth factor (EGF) on peptide transport. EGF decreased apical-to-basolateral fluxes of [(14)C]glycylsarcosine ([(14)C]Gly-Sar) up to 50.2 +/- 3.6% (n = 6) of control values. Kinetic analysis of the fluxes showed that maximal flux (V(max)) of transepithelial transport decreased from 3.00 +/- 0.17 nmol x cm(-2) x min(-1) in control cells to 0.50 +/- 0.07 nmol x cm(-2) x min(-1) in cells treated with 5 ng/ml EGF (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…Furthermore, molecular identification of PEPT1 and PEPT2 provided a novel opportunity to determine the mechanisms of their regulation. For example, it was reported that the intestinal PEPT1 is regulated by various factors, including dietary conditions (Ogihara et al, 1999;Shiraga et al, 1999;Naruhashi et al, 2002), hormones such as insulin, leptin, and thyroid hormone (Buyse et al, 2001;Ashida et al, 2002;Gangopadhyay et al, 2002), epidermal growth factor (Nielsen et al, 2001), development (Shen et al, 2001), and some pharmacological agents (Fujita et al, 1999;Berlioz et al, 2000).…”
mentioning
confidence: 99%
“…Furthermore, molecular identification of PEPT1 and PEPT2 provided a novel opportunity to determine the mechanisms of their regulation. For example, it was reported that the intestinal PEPT1 is regulated by various factors, including dietary conditions (Ogihara et al, 1999;Shiraga et al, 1999;Naruhashi et al, 2002), hormones such as insulin, leptin, and thyroid hormone (Buyse et al, 2001;Ashida et al, 2002;Gangopadhyay et al, 2002), epidermal growth factor (Nielsen et al, 2001), development (Shen et al, 2001), and some pharmacological agents (Fujita et al, 1999;Berlioz et al, 2000).…”
mentioning
confidence: 99%
“…Moreover, although hyperplasia and increased uptake were evident even at 1 wk post-resection, cellular mRNA levels in the ileal enterocyte decreased 3-fold at 1 wk post-resection, while cellular protein levels remained unchanged. This decrease in gene expression of PepT1 despite the strong catabolic stress with a 70% proximal small bowel resection might be related to some counterregulatory hormones (such as epidermal growth factor and triiodothyronine) or other negative regulators of PepT1 gene expression as has been suggested by other in vitro studies (in cell cultures) [23][24]; however, we have no objective data to support this statement. Similar findings of a decrease in jejunal mRNA for PepT1 were reported after enterectomy in rabbits, but no protein or uptake studies were carried out [25].…”
Section: Discussionmentioning
confidence: 66%
“…However, few reports have dealt with the hormonal regulation of PepT1. Insulin could stimulate dipeptide transport by increasing membrane insertion of PepT1 from a preformed cytoplasmic pool [9] , and choleratoxin could decrease dipeptide transport by inhibiting the activity of PepT1 through an increase in intracellular concentration of adenosine 3', 5'-cyclic monophosphate [24] . Strong evidences have demonstrated that growth hormone (GH) was an important growth factor for intestine [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that some hormones metabolically regulated the expression of intestinal dipeptide transporter [8,9] . For example, insulin could increase the membrane population of PepT 1 by increasing its translocation from a preformed cytoplasmic pool [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation